1989
DOI: 10.1093/jnci/81.24.1910
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Carcinogenesis in Man: Solar Ultraviolet B Dose Dependence of Skin Cancer in Maryland Watermen

Abstract: Skin cancer is the most common form of cancer in humans and occurs primarily on sun-exposed areas of the body. In a study of 808 Caucasian Maryland watermen, we examined the prevalence of nonmelanoma skin cancer in relation to age and exposure to solar ultraviolet B (UVB) radiation. For each study subject, the exposure to solar UVB radiation for each year of life after the age of 16 years was calculated. We obtained the data for this analysis by combining a detailed occupational history with laboratory and fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 0 publications
3
51
1
2
Order By: Relevance
“…UVR exposure is the strongest environmental risk factor for developing these cancers. There is a strong relationship between SCC and occupational sun exposure [22][23][24] and continuous, lifelong sun exposure is important in development of SCC. Increased childhood sun exposure and intermittent sunlight exposure resulted in an increased risk of BCC [25][26][27].…”
Section: Eyelidmentioning
confidence: 99%
“…UVR exposure is the strongest environmental risk factor for developing these cancers. There is a strong relationship between SCC and occupational sun exposure [22][23][24] and continuous, lifelong sun exposure is important in development of SCC. Increased childhood sun exposure and intermittent sunlight exposure resulted in an increased risk of BCC [25][26][27].…”
Section: Eyelidmentioning
confidence: 99%
“…MM is the most related death skin cancer; incidence of melanoma is increasing worldwide (1)(2)(3)(4). Melanoma developed from melanocyte, which is pigment-producing cell.…”
Section: Introductionmentioning
confidence: 99%
“…An early study of watermen from the eastern shore of Maryland found that average annual exposure to ambient UVB radiation was strongly correlated with the prevalence of SCC, whereas BCC did not have such a correlation (8), especially in watermen younger than 60 years of age (9). Because of the association between defects in DNA repair genes (10) and the poor DNA repair phenotype (11) that causes a high incidence of BCC and SCC in xeroderma pigmentosum (XP) patients (12), this watermen study provided much enthusiasm for further studying the DNA repair capacity (DRC) as a marker for genetic susceptibility to NMSC in the general population.…”
mentioning
confidence: 99%